Nitrate Regeneration and Loss in the Central Yellow Sea Bottom Water Revealed by Nitrogen Isotopes - Tian, Shichao; Gaye, Birgit; Tang, Jianhui; Luo, Yongming; Lahajnar, Niko; Dähnke, Kirstin; Sanders, Tina; Xiong, Tianqi; Zhai, Weidong; Emeis, Kay-Christian (Frontiers in Marine Science, 2022)
The Yellow Sea (YS) is an epicontinental sea framed by the densely populated mainland of China and the Korean peninsula. Human activities over the last decades resulted in heavily increasing discharge of reactive nitrogen into the YS, which created numerous ecological problems. To elucidate the role of central YS in the cycling of reactive nitrogen, specifically the Yellow Sea Cold Water Mass (YSCWM), we determined nutrient concentrations, dual stable isotopes of nitrate (δ15N-NO_3^- and δ18O-NO_3^-), and stable isotopes of particulate and sedimentary nitrogen in spring and summer, i.e., in biologically inactive and active periods. The nitrate concentration in spring was higher than that in summer in the northern part of the YSCWM, Nitrate increased in the southern part accompanied by a decrease in δ15N-NO_3^- and δ18O-NO_3^-, which are indicative of nitrification that was a significant source of recycled nitrate in the south part of YSCWM. To quantify this regenerated nitrate, we use a mixing model with end members of preformed nitrate in spring and regenerated nitrate in summer, both with their distinct dual isotope values. The results suggest that only 35 % nitrate was a residual of nitrate preformed in spring and 65 % in summer in the southern branch of YSCWM was regenerated. The northern part of YSCWM has low concentrations of dissolved inorganic nitrogen, mainly because of denitrification in sediments. In contrast, the southern pool of YSCWM is a growing reservoir of regenerated terrestrial reactive nitrogen, the addition of which compensates the removal by co-occurring sediment denitrification. In consequence, the southern branch of YSCWM is facing a higher ecological risk than the northern branch, when excess reactive nitrogen discharge from Changjiang River continues at present levels or even increases.